Development of Thematic Monopoly Media to Optimize Early Mathematical Skills in Children Aged 5–6 Years - Ayu Rahayu; Irma Yuliantina; Lilis Suryani (CV. Edujavare Publishing, 2026)
In early childhood education, mathematics is not merely about introducing numbers. This study aimed to develop, determine the feasibility, and examine the effectiveness of Thematic Monopoly media in optimizing the early mathematics skills of children aged 5–6 years. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study was conducted at TK Ar-Rahmah, Terkul Village, Rupat District, Bengkalis Regency, Riau Province, involving 16 children in Group B. Data were collected through observation, interviews, validation sheets, teacher response questionnaires, and field trials. The results of the needs analysis showed that the existing learning media for early mathematics were still limited in terms of interactivity, variation, and contextual relevance, thus requiring the development of a more engaging and developmentally appropriate medium. The feasibility of the product was confirmed by expert validation results, with scores of 85% from the material expert, 90% from the media expert, and 95% from the practitioner, all categorized as very valid. Product trials also showed highly positive results, with an average score of 88.3% across individual, small-group, and large-group trials, while teacher responses during limited implementation reached 89.5%, and classroom activity observations reached 81.75%. Furthermore, the findings demonstrated that the use of Thematic Monopoly media had a positive impact on children’s motivation, participation, enthusiasm, and understanding of early mathematical concepts.